2022
DOI: 10.3389/fpsyg.2022.947948
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality status, anxiety, and depression status of nurses in infectious disease department

Abstract: ObjectiveTo investigate the current status of sleep quality and influencing factors of clinical nurses in infectious disease hospitals, and to provide basis and reference for improving their sleep status and providing psychological support.MethodsUsing convenience sampling method, clinical nurses from a tertiary hospital for infectious diseases were selected as the survey subjects in September 2021. General information questionnaire, Pittsburgh Sleep Quality Questionnaire (PSQI), Generalized Anxiety Disorder S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…impact of social support on nurses, the quality of sleep can still have a positive influence on levels of anxiety and depression. These findings align with previous research in this area [50][51][52][53]. Furthermore, the above epidemiological research has indicated a positive correlation between sleep problems and anxiety and depression.…”
Section: Plos Onesupporting
confidence: 92%
“…impact of social support on nurses, the quality of sleep can still have a positive influence on levels of anxiety and depression. These findings align with previous research in this area [50][51][52][53]. Furthermore, the above epidemiological research has indicated a positive correlation between sleep problems and anxiety and depression.…”
Section: Plos Onesupporting
confidence: 92%
“…Sleep quality was assessed using the PSQI; the assessment has 19 items across 7 component dimensions (subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleeping medications, and daytime dysfunction). 28 Each component score ranges from 0–3 and the global score is the total of the seven component scores (range: 0–21). 29 The global score reflects the severity of sleep disorders: 0–5, none; 6–10, mild; 11–15, moderate; and 16–21, severe.…”
Section: Methodsmentioning
confidence: 99%
“…However, night shifts can disrupt nurses' sleep, affecting their biological clocks and sleep patterns, posing a challenge to their normal circadian rhythms (Alfonsi et al., 2021; Hernandez et al., 2022). International studies have shown that the prevalence of sleep disturbances among night shift nurses is significantly higher compared to the general population (Sun et al., 2019), ranging between 13.5% and 65.8% (Deng et al., 2020; Dong et al., 2020; Xi et al., 2022). Decreased sleep quality can lead to a range of physical health issues, such as headaches, gastrointestinal discomfort, obesity, diabetes, hypertension, coronary heart disease and even breast cancer (Alfonsi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%